The sociodiscursive image of professor Noslen Borges in a post on Instagram - Pinto, Fabiana Aparecida de Almeida; Alvarenga, Thiago Madureira de (Revista Letras Raras, 2023)
In this article, we discuss, as an object of research, the socio-discursive image of Professor Noslen Borges from the metafunctions of the Grammar of Visual Design. The search originated from the perception that research to reach young people on social networks, teachers need to remodel their ethos - the sociodiscursive image - to contribute to the process of mass dissemination of knowledge on Instagram - that is, to reach a large audience. Our general objective was to analyze the ethos designed by the teacher in publications on Instagram and observe how it contributes to the dissemination of knowledge in Portuguese. As a theoretical framework for this work, the research uses authors such as Charaudeau (2016); Grácio (2006). Kress e Van Leeuwen (2006); Lévy (1999), Maingueneau (2008). Finally, playful, fun, fun, in order to complete the most social elements in social networks.